A new species of fossil Calosoma (Coleoptera: Carabidae) from the Geumgwangdong Formation (Early Miocene), South Korea - Lee, Soo Bin; Nam, Gi-Soo (Zootaxa, 2021)
In this paper, a new fossil species of Calosoma (Coleoptera: Carabidae) from the lower Miocene Geumgwangdong Formation, Pohang City, South Korea, is described. Compared with other Miocene Calosoma fossils, Calosoma kimi sp. nov. exhibits different characteristics in particular interval connection and scale patterns on the elytra. It is the first fossil Calosoma recorded from the Korean Peninsula. However, the taxonomic position of C. kimi sp. nov. within Calosoma is not clear at present though it is probably related to the complex of the subgenera Australodrepa, Calodrepa, and Calosoma.